2009
DOI: 10.1002/mrm.22173
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative T2 analysis: The effects of noise, regularization, and multivoxel approaches

Abstract: Typical quantitative T 2 (qT 2 ) analysis involves creating T 2 distributions using a regularized algorithm from region-of-interest averaged decay data. This study uses qT 2 analysis of simulated and experimental decay signals to determine how (a) noise-type, (b) regularization, and (c) region-of-interest versus multivoxel analyses affect T 2 distributions. Our simulations indicate that regularization causes myelin water fraction and intra/extracellular water geometric mean T 2 underestimation that worsens as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 16 publications
4
64
0
Order By: Relevance
“…Bjarnason et al also noted changes in the IEW gmT 2 with noise type: Rician noise caused a reduction in IEW gmT 2 when compared to Gaussian noise [19]. The data presented here show that the IEW gmT 2 is longer when comparing Rician distributed noise data with Gaussian distributed noise data.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Bjarnason et al also noted changes in the IEW gmT 2 with noise type: Rician noise caused a reduction in IEW gmT 2 when compared to Gaussian noise [19]. The data presented here show that the IEW gmT 2 is longer when comparing Rician distributed noise data with Gaussian distributed noise data.…”
Section: Discussionsupporting
confidence: 63%
“…Representative T 2 distributions are shown in Fig 9. Previous research suggested that changing the noise type from Rician to Gaussian would have dramatic effects on the measured MWF [19]; most notably an increase in MWF would occur as SNR decreases. No significant change was observed for the data presented here in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The typical qT2 analysis proceeds as follows: (1) a multiecho T2 MR image is acquired; (2) a region of interest (ROI) is specified on the image; (3) decay data within the ROI are averaged; and (4) a T2 distribution is created by fitting a sum of weighted exponential decays to the averaged decay data. 20 To make the fit more resilient to noise, a regularization routine is often applied.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the regularization causes underestimation of the myelin water fraction (MWF), and this error increases as the signal-tonoise ratio decreases. 20 Fourth, the analysis often requires multiple software programs with different interfaces and input requirements. The main objective of this study was to overcome these limitations and establish an advanced analytical platform for complex pathologies, in vivo.…”
Section: Introductionmentioning
confidence: 99%